2017
DOI: 10.1111/bjdp.12195
|View full text |Cite
|
Sign up to set email alerts
|

‘Will I want these stickers tomorrow?’ Preschoolers’ ability to predict current and future needs

Abstract: Between 3 and 5 years of age, children develop the ability to plan for their own and others' future needs; however, they have great difficulty predicting future needs that conflict with current ones. Importantly, this ability has only been tested in the domain of physiological states (e.g., thirst). Therefore, it is still an open question whether in a different context preschoolers can disengage from their current needs to secure a different future one. In a Resource Allocation task, 4- and 5-year-olds had to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…Control questions would be useful in future work to confirm children's understanding of both the experimenter's baseline preference and their current state. More generally, replicating current findings with states other than thirst, and from perspectives other than that of the experimenter, will be important in determining if similar effects exist when making future predictions in different contexts (see Martin‐Ordas, , for a novel paradigm to examine current‐future state conflict outside the physiological domain).…”
Section: Discussionmentioning
confidence: 84%
“…Control questions would be useful in future work to confirm children's understanding of both the experimenter's baseline preference and their current state. More generally, replicating current findings with states other than thirst, and from perspectives other than that of the experimenter, will be important in determining if similar effects exist when making future predictions in different contexts (see Martin‐Ordas, , for a novel paradigm to examine current‐future state conflict outside the physiological domain).…”
Section: Discussionmentioning
confidence: 84%
“…However, part of the utility of the Pretzel task is that thirst is a powerful motivational state that impacts future choices. Nonetheless, EpF tasks that mimic the current-future state conflict that exists in the Pretzel task have been developed outside the physiological domain (see Belanger et al, 2014; Cheke & Clayton, 2019 ; Martin‐Ordas, 2017 ). Future work should examine the extent to which manipulations surrounding episodic simulation and motivation might increase EpF in the non-physiological domains.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that 8- to 13-year-old children and even young adults seem to fall prey to the presentism bias in the Pretzel task ( Kramer et al, 2017 ). Thus, so-called induced-state EpF does not show the usual developmental progression compared to other EpF tasks where a current state does not conflict with a future state (e.g., Atance & Meltzoff, 2005 ; Suddendorf et al, 2011 ) and potentially where the current-future state conflict is outside the physiological domain (e.g., Bélanger et al, 2014 ; Martin‐Ordas, 2017 , although see Lee & Atance, 2016 ). Interestingly, it seems to be the case that older children and perhaps even adults perform similarly to 3-year-olds on this task.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations